Preparative separation of underivatized amino acids for compound-specific stable isotope analysis and radiocarbon dating of hydrolyzed bone collagen. - Tripp, J; McCullagh, J; Hedges, R (2006)
Analysis of stable and radioactive isotopes from bone collagen provides useful information to archaeologists about the origin and age of bone artifacts. Isolation and analysis of single amino acids from the proteins can provide additional and more accurate information by removing contamination and separating a bulk isotope signal into its constituent parts. In this paper, we report a new method for the separation and isolation of underivatized amino acids from bone collagen, and their analysis by isotope ratio MS and accelerator MS. RP chromatography is used to separate the amino acids with nonpolar side chains, followed by an ion pair separation to isolate the remaining amino acids. The method produces single amino acids with little or no contamination from the separation process and allows for the measurement of accurate stable isotope ratios and pure samples for radiocarbon dating.